Metaphor and metonymy as a means of economy of expression - Kos, Petr (The Slovak Association for the Study of English, 2019)
This paper deals with metaphor and metonymy in word formation from an onomasiological perspective. As the treatment of both metaphor and metonymy in word formation has previously been rather neglected, it aims to show that they play an indispensable role in the formation of new naming units, both morphologically simple and complex, and that they are instrumental in achieving the economy of expression and effability in instances where literal description might fail to do so. The discussion of metaphor and metonymy in word formation is based on an onomasiological model originally based on that of Štekauer’s, with some major modifications, and the examples used for illustration are taken from the realm of natural organisms.
Metafora a metonymie jako prostředek ekonomičnosti výrazu
Keywords: onomasiology; word formation; metaphor; metonymy; economy of expression; onomaziologie; slovotvorba; metafora; metonymie; ekonomičnost výrazu